Identify Bumiputera demographic profile of mushroom market : Kota Samarahan / Donny Jalong Ngau - Jalong Ngau, Donny (2009)
Mushroom is a good industry in Malaysia. A lot of Malaysian has been involved in this industry to earn their living and as a part time. This research will help me to get the information about the consumer towards mushroom. With the information I can plan how to market the mushroom. This study is essential to make the mushroom business in Kota Samarahan success especially at Desa Ilmu area. The limitations this research such as constraints, financial constraints and difficulty in gaining from respondents. Research design for this study is exploratory research because it attempt to explore and indentify the demographic profile of potential mushroom market. From this study, it will found the consumer profile and market towards mushroom. Therefore, this information very helpful for marketing the mushroom at Kota Samarahan. As a result recommendation can become a guideline to me to become more competitive to sustain in this business.